2011
DOI: 10.1590/s0080-62342011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Estado neurológico e cognição de pacientes pós-acidente vascular cerebral

Abstract: RESUMOObjeti vou-se investi gar por meio de uma equipe multi disciplinar o estado neurológi-co e o desempenho cogniti vo de pacientes pós-AVC mediante um estudo transversal com 45 pacientes em processo de reabilitação após um AVC agudo. Uti lizaram-se como instrumentos de coleta de dados uma fi cha de avaliação, o Mini Mental--MEEM e o Nati onal Internati onal Health Stroke Scale-NIHSS. Amostra predominantemente feminina (55,6%), AVC Isquêmico (86,7%), Hemisfério cerebral direito (60%) e Escolarizados (68,8%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
18

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 18 publications
2
16
0
18
Order By: Relevance
“…Most participants in this study were married, as verified also in three other studies: one with 289 people who have had stroke in working age, accompanied by the Unified Health System (SUS) in the city of Recife, Pernambuco (PE) 18 ; another study conducted in Natal, Rio Grande do Norte (RN), with a group of 45 people who had stroke and varied age 19 , and a third performed in Jequié, Bahia (BA), which involved a group of 20 people diagnosed with stroke with different ages 20 . Related to TBI, a study conducted with a group of 56 participants in São José do Rio Preto, São Paulo (SP), showed that 56% were single and 40% were married 21 .…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Most participants in this study were married, as verified also in three other studies: one with 289 people who have had stroke in working age, accompanied by the Unified Health System (SUS) in the city of Recife, Pernambuco (PE) 18 ; another study conducted in Natal, Rio Grande do Norte (RN), with a group of 45 people who had stroke and varied age 19 , and a third performed in Jequié, Bahia (BA), which involved a group of 20 people diagnosed with stroke with different ages 20 . Related to TBI, a study conducted with a group of 56 participants in São José do Rio Preto, São Paulo (SP), showed that 56% were single and 40% were married 21 .…”
supporting
confidence: 76%
“…Many studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] indicate that the most common cause of ABI are CVA, and the derivatives of ischemic events (ICVA) the most frequent, as indicated by the data in this study, in which 41.1% of subjects were affected by ischemic stroke. ICVA has as a main risk factor the SAH, DM, hypercholesterolemia (high cholesterol), smoking and genetic factors 29 .…”
Section: Discussionmentioning
confidence: 85%
“…In this study, the mean found at the MMSE among the 104 initial participants was 23.1 points (±5.54), a different value compared to that of another study that found a lower mean. (11) In this sample, 26% had cognitive deficit, a lower value than the 45% prevalence of patients with this type of deficit found in literature. (12) These results can be attributed to the fact that this study's participants had more years of schooling than those found in similar research, which influences an increase in scoring.…”
Section: Discussionmentioning
confidence: 50%
“…The presence of disturbances in cognition is an important complication of recovery, directly affecting the process of rehabilitation and recovery of the patient. 3 Cognitive dysfunctions may interfere with an individual's ability to understand precisely all parts of their condition, since a cognitively impaired patient may have difficulty keeping a memory of past events and associating related information. 4 Cognitive screening instruments are quick and easy to perform tests that provide approximate characterization of various cognitive functions and are indicated for use in distinguishing between normal and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%